Donskerâs Delta Functional of Stochastic Processes with Memory - Herry Pribawanto Suryawan (Journal of Mathematical and Fundamental Sciences, 2019)
A class of stochastic processes with memory within the framework of the Hida calculus was studied. It was proved that the Donsker delta functionals of the processes are Hida distributions. Furthermore, the probability density function of the processes and the chaos decomposition of the Donsker delta functional were derived. As an application, the existence of the renormalized local times in an arbitrary dimension of the Riemann-Liouville fractional Brownian motion as a white noise generalized function was proved.